Phase equilibria in Ho-Fe-Sn ternary system at 670 K - Romaka, L.; Stadnyk, Yu.; Romaka, V. V.; Horpenyuk, A. (Physics and Chemistry of Solid State, 2020)
Interaction between the components in the Ho-Fe-Sn ternary system was studied using X-ray diffractometry, metallography and electron microprobe analysis. Isothermal section of the phase diagram was constructed at 670 K over the whole concentration range. Component interaction in the Ho-Fe-Sn system at 670 K results in the existence of one ternary compound HoFe6Sn6 which crystallizes in the YCo6Ge6 structure type (space group P6/mmm, a=0.53797(2), c= 0.44446(2) nm). The interstitial-type solid solution HoFexSn2 (up to 8 at.% Fe) based on the HoSn2 (ZrSi2-type structure) binary compound was found. Solubility of Sn in the HoFe2 binary (MgCu2 structure type) extends up to 5 at. %.